Investigating Impacts of Local Pressure and Temperature on CVD Growth of Hexagonal Boron Nitride on Ge(001)/Si - Max Franck; Jarek Dabrowski; Markus Andreas Schubert; Dominique Vignaud; Mohamed Achehboune; Jean‐François Colomer; Luc Henrard; Christian Wenger; Mindaugas Lukosius (Advanced Materials Interfaces)
Abstract The chemical vapor deposition (CVD) growth of hexagonal boron nitride (hBN) on Ge substrates is a promising pathway to high‐quality hBN thin films without metal contaminations for microelectronic applications, but the effect of CVD process parameters on the hBN properties is not well understood yet. The influence of local changes in pressure and temperature due to different reactor configurations on the structure and quality of hBN films grown on Ge(001)/Si is studied. Injection of the borazine precursor close to the sample surface results in an inhomogeneous film thickness, attributed to an inhomogeneous pressure distribution at the surface, as shown by computational fluid dynamics simulations. The additional formation of nanocrystalline islands is attributed to unfavorable gas phase reactions due to the radiative heating of the injector. Both issues are mitigated by increasing the injector‐sample distance, leading to an 86% reduction in pressure variability on the sample surface and a 200 °C reduction in precursor temperature. The resulting hBN films exhibit no nanocrystalline islands, improved thickness homogeneity, and high crystalline quality (Raman FWHM = 23 cm−1). This is competitive with hBN films grown on other non‐metal substrates but achieved at lower temperature and with a low thickness of only a few nanometers.